A Comparative Analysis of Cognitive Behavioral Therapy and Mindfulness-Based Cognitive Therapy for Enhancing Weight Management and Physical Activity in Obese Individuals with Coronary Artery Disease - Ishtiaq, Hifza; Zafar, Alina; Ahmed, Saqlain; Khattak, Iftikhar; Ijaz Raja, Ayesha; Kant, Bashir ur Rehman (Indus Journal of Bioscience Research, 2024)
Background: Obesity is a major modifiable risk factor for cardiovascular diseases (CVDs). It contributes to enhance the mortality and morbidity. Lifestyle interventions are basic, psychological barriers like poor motivation and emotional eating and stress often affect sustained change in behavior. Methodology: This study used a quasi-experimental approach with a pre-test and post-test with a control group. The study involved 30 participants (15 in cognitive behavioral therapy (CBT) and 15 in MBCT). The trial recruited adults aged 30-60 with diagnosed coronary artery disease (CAD), Body Mass Index >30kg/m2 and a willingness to attend 1 weekly therapy sessions. A multivariate analysis of variance (ANOVA) was used to examine differences within and between groups. Results: Among the participants, 66.7% are married and 33.3% are single, indicating a heterogenous marital composition. In terms of education. At the follow-up, the MBCT group had somewhat higher reductions (30.7±1.8) than the CBT group (31.5±1.9), indicating a possible advantage for mindfulness-based treatments in sustaining weight loss. The MBCT group showed somewhat larger improvement (3.1 ± 0.7) than the group receiving cognitive behavioral therapy (2.8 ± 0.6). At follow-up, the group receiving MBCT maintained higher activity levels (3.4 ± 0.7) compared to the CBT group (3.0 ± 0.8). Conclusion: Both CBT and mindfulness-based cognitive therapy significantly lowered the body mass index with time, with MBCT demonstrating slightly higher reduction at follow-up indicating a possible advantage in maintaining loss of weight. Mindfulness cognitive therapy showed a crucial advantage in promoting higher longer term activity levels compared to cognitive behavioral therapy.